2017
DOI: 10.1007/s10995-017-2292-1
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Romani Women’s Autonomy and Timing of Pregnancy in Serbia and Macedonia

Abstract: Background Roma are Europe's largest minority population. Serbia and Macedonia have the greatest proportion of Roma outside of the European Union. Our objective was to examine women's agency and how it related to desired timing of pregnancy among Romani women in Macedonia and Serbia. Methods We surveyed 410 Romani women who had given birth in the last 2 years between November 2012-February 2013 in Serbia and Macedonia using purposeful snowball sampling. Log-Poisson models were used to examine the association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Engaging with minority groups on healthcare issues is important if the full range of human capabilities are to flourish (Nussbaum, 2011). One such minority group is Roma people who live worldwide and are Europe's largest and the most marginalized ethnic minority (Stojanovski, Janevic, Kasapinov, Stamenkovic, & Jankovic, 2017). According to the European Commission in 2010, it has been estimated that there are between 10 and 15 million Roma people across Europe.…”
Section: Context: Roma In Northern Irelandmentioning
confidence: 99%
“…Engaging with minority groups on healthcare issues is important if the full range of human capabilities are to flourish (Nussbaum, 2011). One such minority group is Roma people who live worldwide and are Europe's largest and the most marginalized ethnic minority (Stojanovski, Janevic, Kasapinov, Stamenkovic, & Jankovic, 2017). According to the European Commission in 2010, it has been estimated that there are between 10 and 15 million Roma people across Europe.…”
Section: Context: Roma In Northern Irelandmentioning
confidence: 99%
“…Roma Girls Motherhood (RGM) is deeply embedded in a tangle of multiple discriminations and used by certain sectors of European society to validate the stereotyping and rejection of Roma [ 1 , 2 , 3 , 4 , 5 ]. Research in this area consistently affirms that RGM is one of the factors that impoverishes the life of girls, increases the risks of suffering physical and mental health problems, makes them vulnerable to intimate partner violence, and prevents them from remaining in the educational system and successfully inserting themselves into the labor market [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many studies have shown that child motherhood is often associated with emotional stability, purpose, and responsibility as well as a strong sense of belonging to a cultural community [ 7 , 18 , 19 ]. This is especially explanatory in impoverished Roma communities where girls happily assume motherhood in return for acquiring mattering despite the hard limitations entailed in their lives and without questioning why their parents and close relatives promote it despite knowing the limitations this poses in their lives [ 2 , 4 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previously published literature from this area, the authors have highlighted that empowering Roma women to be involved in their health care leads to their stronger independence regarding the decision of pregnancy timing (2). Therefore, guided primary care can help Roma women being more aware of their reproductive health options.…”
mentioning
confidence: 99%